2019
DOI: 10.3390/ph12040147
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Experimental Models for Studying Influenza Proteins, Host–Virus Interactions and Anti-Influenza Drugs

Abstract: Ninety years after the discovery of the virus causing the influenza disease, this malady remains one of the biggest public health threats to mankind. Currently available drugs and vaccines only partially reduce deaths and hospitalizations. Some of the reasons for this disturbing situation stem from the sophistication of the viral machinery, but another reason is the lack of a complete understanding of the molecular and physiological basis of viral infections and host-pathogen interactions. Even the functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 307 publications
(334 reference statements)
0
13
0
Order By: Relevance
“…The immune system of ferrets has not been studied in detail [ 31 , 54 ]. The immune systems of guinea pigs, Syrian hamsters, tree shrews, and swine, compared to murine species (mice and rats), are more similar to the human immune system [ 44 , 50 , 51 , 53 , 63 , 64 , 65 ]. Non-human primates have high genetic homology to humans and more than 90% amino acid similarity is found in the cytokines of humans and non-human primates [ 47 , 66 , 67 ], but differences in the sialic acid-recognizing immunoglobulin-like lectins are observed [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The immune system of ferrets has not been studied in detail [ 31 , 54 ]. The immune systems of guinea pigs, Syrian hamsters, tree shrews, and swine, compared to murine species (mice and rats), are more similar to the human immune system [ 44 , 50 , 51 , 53 , 63 , 64 , 65 ]. Non-human primates have high genetic homology to humans and more than 90% amino acid similarity is found in the cytokines of humans and non-human primates [ 47 , 66 , 67 ], but differences in the sialic acid-recognizing immunoglobulin-like lectins are observed [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Influenza virus belongs to the Orthomyxoviridae family, which are negative-sense single-stranded RNA viruses that cause respiratory diseases. Yeast has been used to study the transcription and replication of the viral genome, polyadenylation, translational control, and mechanism of viral budding out of the cell (Chua et al 2019). The transcriptional elongation factor, Tat stimulatory factor 1 (Tat-SF1) homolog of yeast CUS2, was identified as an essential factor for synthesizing the influenza viral genome in yeast (Naito et al 2007).…”
Section: Rna Virusesmentioning
confidence: 99%
“…Coronavirus pandemic of 2019 caused by severe acute respiratory syndrome coronovirus-2 (SARS-CoV-2) is an excellent recent example where studies of similar corona viruses in yeast and other model systems not only enabled researchers to rapidly understand the biology of the virus but also helped in developing antivirals/vaccines (Pollet et al 2020). Virus research has undoubtedly benefitted using alternative hosts such as Caenorhabditis elegans, Drosophila, Zebra fish, mammalian cell lines, mouse models, and yeast with each one having its own pros and cons (Chua et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A549 human lung adenocarcinoma epithelial cell line is a commonly used tool to investigate the interactions between virus and host, the biochemistry of viral proteins, and to analysis genes that are overexpressed to suppress viral infections, to perform large-scale drug screening, for example, screening for CRISPR activation, [ 34 ]. It was previously demonstrated that TCM Reseda odorata (木犀草) decreased the Caspase-9, Caspase-8 and Caspase-3 expression in A549 cells infected with H1N1 virus [ 35 ] and Chuanxiong Rhizoma (川芎) [ 36 ].…”
Section: Experimental Modelsmentioning
confidence: 99%